Greener Method to Obtain a Key Intermediate of Vitamin E over Cu-ZSM-5 - Saux, Clara (2014)
The catalytic oxidation of 2,3,5-trimethylphenol was performed over transition metals modified ZSM-5 zeolites employing hydrogen peroxide as oxidant under mild reaction conditions. Catalysts samples were characterized by several techniques (XRD, FTIR, BET, AA) and cristallinity and orthorhombic symmetry were confirmed for all of them. Best catalytic results were obtained for Cu-ZSM-5 sample, so further activity studies were done over this material. 2,3,5-trimethyl-1,4-benzoquinone was obtained as the main product of the selective oxidation. Reaction parameters (nature of the solvent, hydrogen peroxide concentration, reaction time, catalyst mass, substrate initial concentration and reaction temperature) were evaluated to reach the optimum reaction conditions. According to the obtained results, an apparent activation energy of 52.33 kJ/mol was calculated.